Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To be able to solve the given exponential equation, let's make sure first that they will have the same base.
As of now, their bases are 27 and 81. Let's rewrite these two numbers in such a way that they will have the same base.
[tex]\begin{gathered} 27=3^3 \\ 81=3^4 \end{gathered}[/tex]From this, we can rewrite the exponential equation into:
[tex]3^{3(x-2)}=3^{4(x-1)}[/tex]Since both sides now have the same base, we can now equate the exponents of each base.
[tex]3(x-2)=4(x-1)[/tex]Let's simplify the equations on both sides by distributing 3 and 4 to the terms inside each respective parenthesis.
[tex]3x-6=4x-4[/tex]Let's subtract 3x on both sides of the equation.
[tex]\begin{gathered} 3x-6-3x=4x-4-3x \\ -6=x-4 \end{gathered}[/tex]Let's add 4 on both sides of the equation.
[tex]\begin{gathered} -6+4=x-4+4 \\ -2=x \end{gathered}[/tex]Therefore, the value of x is -2.
[tex]\begin{gathered} 27^{-2-2}=81^{-2-1} \\ 27^{-4}=81^{-3} \\ \frac{1}{27^4}=\frac{1}{81^3} \\ \frac{1}{531,441}=\frac{1}{531,441} \end{gathered}[/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.